Four-Year Outcomes of Unprotected Left Main Lesion PCI with Self-Apposing Stents versus Balloon-Expandable Stents - Predescu Lucian; Bucsa Adrian; Croitoru Marian; Mereuta Adrian; Platon Pavel; Postu Marin; Zarma Lucian; Dorobantu Dan; Lichiardopol Leonard; Predescu Alexandra; Ginghina Carmen; Deleanu Dan (Sciendo, 2022)
Left main percutaneous coronary intervention (PCI) has been established as an effective and safe treatment option for left main coronary artery disease. There are data suggesting that different stent platforms can impact the outcomes after left main PCI. The aim of current study was to compare the four-year outcomes of patients with left main stenosis treated by PCI with a balloon-expandable stent or a self-apposing stent.